EKSPERIMENTASI MODEL PEMBELAJARAN THINK-PAIR-SHARE (TPS) DIMODIFIKASI DENGAN MIND MAPPING PADA MATERI KUBUS DAN BALOK DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA SISWA SMP NEGERI KELAS VIII Se-KABUPATEN PEMALANG TAHUN 2012/2013 - Siwi, Julian Reza; Mardiyana, Mardiyana; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this study were to find out on the topic of cube and cuboid: (1) which was better between TPS Modified Mind Mapping (TPSMod), TPS or Direct model that produce learning achievement; (2) which one had better learning achievement between students with high, medium or low categories of mathematics creativity learning; (3) at each category of mathematicsÂ creativity learning, which was better between TPSMod, TPS or Direct model that produce learning achievement; and (4) at each model, which one had better learning achievement between students with high, medium or low categories of mathematics creativity learning. This study was a quasi-experimental with 3Â´3 factorial design. The population was all of students in eigth grade of State Junior High School in Pemalang Regency on Academic Year 2012/2013. The samples were taken by using a stratified cluster random sampling technique. The samples was students in eight grade of SMP Negeri 1 Randudongkal, Moga and Pulosari. The instrument of this study were mathematics creativity learning questionnaire and learning achievement test. The questionnaire tryout included content validity, internal consistency and reliability, and the test tryout included content validity, difficulty level, discrimination power, and reliability. Before the experiment was done, the balance of prior knowledge was examined by using unbalanced one way anova test. The hypothesis test used unbalanced two ways anova. Test requirements included normality test used Lilliefors method and the homogeneity test used the Bartlett test. The results of the study were as follows: (1) the TPSMod model produce the learning achievement better than the TPS and direct learning, the TPS model give the same learning achievement as the direct learning; (2) the high and medium categories of mathematics creativity learning have the same learning achievement, and both of category of mathematics creativity learning have better learning achievement from low categories of mathematics creativity learning; (3) at each categories of mathematics creativity learning, theTPSMod model produce the learning achievement better than the TPS and direct learning, the TPS give the same learning achievement as the direct learning; and (4) at each models, the high and medium categories of mathematics creativity learning have the same learning achievement, and both of category of mathematics creativity learning have better learning achievement from low categories of mathematics creativity learning.Keywords: Learning Achievement, TPS Modified by Mind Mapping , Mathematics Creativity Learning